Wrongful Interference of Police in Civil Transactions and the Remedies for Aggrieved Persons - Saredau, Daniel P.; Okpa, Ujong Bassey (ABUAD Law Journal, 2022)
Though established under section 214 of the 1999 Constitution of the Federal Republic of Nigeria, the provisions on the functions, powers, administration, and structure of the Nigeria Police Force are as contained in the Nigeria Police Act, 2020. But, despitesection 32(2) of the Police Act and section 8(2) of the Administration of Criminal Justice Act (2015) providing that a person shall not be arrested merely on a civil wrong or breach of contract, and the plethora of judicial authorities deprecating this practice, there continues to be a swash of cases in which the police meddle with civil claims. In the result, the police often, wrongly, turn itself into a debt recovery agency, an enforcer of contracts, or a forum for settling civil claims.Using doctrinal methodology and a discursive research design, this study examines the law on the issue. The study finds that there are legal remedies available for a person who feels aggrieved with police interference in civil claims. The remedies discussed are action for malicious prosecution, action for false imprisonment, fundamental rights enforcement action, and action under the Anti-torture Act.Overall, the studydissuades citizens from resort to the police for civil claims, and encourages the police to desist from wrongful interference in civil claims.